The body schema: neural simulation for covert and overt actions of embodied cognitive agents. Issue 19 (February 2021) - Morasso, Pietro; Mohan, Vishwanathan
Abstract : This brief commentary on the general topic of 'body schema' is focused on its computational role, as an internal model that integrates proprioceptive information, for allowing embodied cognitive agents to carry out the neural simulation of covert and overt actions in a unitary manner. The discussion takes inspiration from the vintage but still valid seminal observation by Marr and Poggio that, in order to understand cognitive agents, both human and artificial, we should consider them as Generalized Information Processing Systems, to be analyzed along three levels: computational, algorithmic, and implementation. Accordingly, the body schema concept is briefly analyzed along this line, with the purpose of outlining a cognitive architecture that links embodied cognition with motor control through the body schema.